Functional status of pituitary-ovarian system in mature rats under long-term impact of heavy metals and non-hormonal correction - Hryntsova, Natalia; Romanyuk, Anatoliy (ScienceRise: Biological Science, 2017)
Aim of the research is the study of functional features of the pituitary-ovarian system of female rats under the long-term influence of the combination of low doses of salts of heavy metals and non-hormonal correction by vitamin E. Materials and methods. The experimental study was carried out on 30 white mature female rats with the mass 200–230 g, age 5–7 months that during 30, 60 and 90 days respectively underwent the microelementosis modeling. The animals received ordinary drinking water, saturated with the combination of salts of heavy metals: zinc (ZnSO4·7H2O) – 5 mg/l, copper (CuSO4·5H2O) – 1 mg/l, iron (FeSO4) – 10 mg/l, manganese (MnSO4·5H2O) – 0,1 mg/l, lead (Pb(NO3)2) – 0,1 mg/l and chrome (K2Cr2O7) – 0,1 mg/l. The correction of revealed reconstructions in the pituitary-ovarian system was carried out using the non-hormonal corrector, vitamin E. The method of immune-enzyme method of the study (automatic chemiluminescent immune analysis) with the determination of luteinizing, follicles-stimulating hormones, progesterone, estradiol in peripheral blood serum of the studied animals was used. Results of research. The functional state of the hypophysis and ovary underwent functional reconstructions in the context of the course of general adaptive syndrome that has a certain dynamics of secretory changes and phases. The level of luteinizing hormone in blood serum of intact rats and experimental animals on 30, 60 and 90-the day of the experiment remained practically stable and was <0,1 mIUn/ml. FSH concentration on 30 day in the rat organism increased in 2,09 times (р≥0,05), but at all following terms FSH level decreases to the indices of control animals. Progesterone level on 30-th and 60-th day of the experiment dynamically decreased, respectively in 2 times (р<0,001, t=13,77418) and in 2,44 times (р<0,001, t=9,838906) comparing with the control. On 90 day of the experiment progesterone content in blood serum of rats remains less that the indices of control animals in 1,2 times (р<0,001, t=3,731171). Salts of heavy metals have the negative influence on estradiol secretion by ovary. On 30-th and 60-th day of the experiment estradiol level decreases comparing with the indices of control animals in 3,44 times (р<0,001, t=75,43049). On 90-the day estradiol level increases in 1,34 times (р<0,001, t=10,0) comparing with the indices of animals of 60 day term of the experiment, remains less than the indices of control animals in 2,56 times (р<0,001, t=44,41311). The use of vitamin E as a corrector positively influences the pituitary-ovary system. There is observed the increase of LH amount, circulating in blood by 41 %, and progesterone in 1,46 times comparing with the indices of control animals. Conclusions. Salts of heavy metals cause the complex of negative changes, that lead to essential functional disorders in the adenohypophysis and ovary of mature rats. The revealed reconstructions are in the direct dependence on the experiment terms, are characterized by the phased course of the general adaptive syndrome and deep imbalance in the work of the pituitary-ovary system. Antioxidant L-tocopherol revealed the reliable stress-protective effect on the course of the second phase of the estral cycle of mature female rats